STATE-OF-THE-ART EXPERIMENTS AND TRENDS IN RHYTHM INSTRUMENTS: ताल वाद्यों में अधुनातन प्रयोग एवं प्रवृत्तियाँ - Singh, Gyanasagar (International Journal of Research -GRANTHAALAYAH, 2015)
In music, rhythm is of equal importance in all the three modes - singing and dancing. Rhythm discharges discipline in music. This systematic and disciplinary rhythm system creates musical bliss. In its absence, there is no beauty and meaning in music without rhythm. Hearing of unsympathetic music instills sadness in the heart. The rhythm is a symbol of vibrancy and vibrancy. संगीत में तीनों अंगो-गायन वादन और नृत्य इन तीनों विधाओं में ताल का समान महत्व है। ताल संगीत में अनुशासन का निर्वहन करता है। यह नियमबद्ध और अनुशासनात्मक ताल व्यवस्था ही सांगीतिक आनंद का सृजन करती है। इसके अभाव में अर्था त ताल रहित संगीत में सौंदर्य तथा सार्थ कता नहीं रह जाती है। अनिबद्ध संगीत के श्रवण से हृदय में उदासीनता सीछा जाती है। ताल जीवंतता और उमंग का प्रतिक है।